2008
DOI: 10.1177/1741143208095788
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Free Primary Education in Kenya

Abstract: Free primary education (FPE) is widely assumed to be required to ensure that the poor gain enrolment. After the introduction of FPE (from January 2003) in Kenyan schools, huge increases in enrolment were officially reported. However, our research, conducted 10 months after the introduction of FPE in and around the informal settlement of Kibera, Nairobi, suggests a less beneficial outcome. Although enrolment had increased in government primary schools, this needs to be balanced against a much larger reported de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(15 citation statements)
references
References 8 publications
1
14
0
Order By: Relevance
“…Despite the provision of school fees, 36 percent of intervention participants (compared to 94% of the control group) reported that they were absent due to a lack of school fee. Although primary school is tuition-free and compulsory, there are additional expenses that families must cover such as registration and admission fees, additional uniforms, school building funds, PTAs, extra tutorials, and others (Kagotho, 2016; Mungai, 2012; Tooley et al, 2008). These costs are even larger in secondary school, and especially at boarding schools which require additional supplies and travel costs.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the provision of school fees, 36 percent of intervention participants (compared to 94% of the control group) reported that they were absent due to a lack of school fee. Although primary school is tuition-free and compulsory, there are additional expenses that families must cover such as registration and admission fees, additional uniforms, school building funds, PTAs, extra tutorials, and others (Kagotho, 2016; Mungai, 2012; Tooley et al, 2008). These costs are even larger in secondary school, and especially at boarding schools which require additional supplies and travel costs.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the cost of children attending secondary schooling is often much higher than attending primary school so we expect the impact of primary school‐age children on education expenditures to be different than that of secondary school‐age children. Previous case studies have reported that the quality of public schools, or at least perceptions of quality, declined since the adoption of FPE (Oketch, Mutisya, Ngware, Ezeh & Epari, ; Tooley, Dixon, & Stanfield, ). While the availability of free primary schooling may reduce household educational expenditures, households and their extended families are also making a decision about the quality of education they receive.…”
Section: Empirical Specificationmentioning
confidence: 99%
“…Kenya has two main categories of education institutions: public and private schools (Tooley, Dixon, & Stanfield, 2008). The present study was part of a larger project focusing on language produced in cross‐age peer‐tutoring classroom interactions at a private co‐education school, Akili Academy, in Nairobi, Kenya.…”
Section: Methodsmentioning
confidence: 99%